Thermal energy storage coupled with PV panels for demand side management of industrial building cooling loads. (1st January 2017) - Arteconi, Alessia; Ciarrocchi, Eleonora; Pan, Quanwen; Carducci, Francesco; Comodi, Gabriele; Polonara, Fabio; Wang, Ruzhu
Highlights: Use of a TES for industrial building cooling loads management is investigated. TES is used for load shifting to weekends to recover surplus PV electricity. TES increases the energy use of the HVAC system. Energy costs are reduced thanks to PV electricity recovery. Abstract: Due to their non-deterministic behaviour, renewable energies are defined as non-dispatchable energies and are largely coupled with energy storage systems to overcome the problem of matching energy production and demand. Hence, in the energy efficiency and conservation field there is growing interest towards energy storage systems, especially when combined with the demand side management (DSM) concept, representing DSM the possibility of shaping end user electricity consumption. In this work an existing installation of a thermal energy storage (TES) system coupled with heat pumps in an industrial building is presented and a dynamic simulation model is built to represent its behaviour. Simulations are performed to show the load shifting potential of such storage and costs and energy use are assessed for different configurations, in order to evaluate the viability of this TES application. In particular the demand side strategy considered is aimed at shifting energy demand for cooling to weekend daytime to recover surplus PV electricity or otherwise to off peak hours to profit from lower electricity tariffs. It is found that the use of TES implies increased energy demand, while costs can decrease when electricity tariffs with a considerable difference between on peak and off peak rates are applied. Furthermore the integration with renewable sources for electricity production, such as PV panels, makes the installation of TES economically interesting independently of the electricity tariff in place. However the more relevant aspect for the overall economic feasibility of such installation is the initial capital investment.